Temperature‐Responsive 4D Liquid Crystal Microactuators Fabricated by Direct Laser Writing by Two‐Photon Polymerization. Issue 2 (4th February 2022) - del Pozo, Marc; Delaney, Colm; Pilz da Cunha, Marina; Debije, Michael G.; Florea, Larisa; Schenning, Albert P. H. J.
Abstract : Untethered Microactuators In article number 2100158, Marc del Pozo, Larisa Florea, Albert P. H. J. Schenning, and co‐workers present a new liquid crystalline photoresist for the creation of untethered microactuators using direct laser writing by two‐photon polymerization. The presented responsive microstructures have a high crosslink density that facilitates the creation of complex 3D geometries which exhibit temperature induced anisotropic shape changes. Such untethered microactuators are attractive to fields including microfluidics or medicine.